2009
DOI: 10.1007/s00408-009-9187-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Measurement in Chronic Cough

Abstract: Chronic cough is a common symptom-based diagnostic challenge for primary care physicians and respiratory specialists. Measurement of exhaled nitric oxide is a convenient, reproducible, and inexpensive point-of-service test. It can simplify the evaluation process of chronic cough by providing information regarding the state of airway inflammation. If exhaled nitric oxide is elevated, this is predictive of a favorable response to inhaled corticosteroids. This has the effect of reducing empirical trials for cough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Fractional exhaled nitric oxide (FENO) is a biomarker of airway inflammation and it has been confirmed that several airway diseases such as asthma 1, 9597, allergies 98100, chronic cough 101, 102, atopic eczema 103, obstructive sleep apnea syndrome 104, and tuberculosis 105 are related to FENO level. In the past twenty years, FENO has been used as a useful clinical tool for diagnosis of airway diseases 106.…”
Section: Application Of No Electrochemical Sensorsmentioning
confidence: 99%
“…Fractional exhaled nitric oxide (FENO) is a biomarker of airway inflammation and it has been confirmed that several airway diseases such as asthma 1, 9597, allergies 98100, chronic cough 101, 102, atopic eczema 103, obstructive sleep apnea syndrome 104, and tuberculosis 105 are related to FENO level. In the past twenty years, FENO has been used as a useful clinical tool for diagnosis of airway diseases 106.…”
Section: Application Of No Electrochemical Sensorsmentioning
confidence: 99%
“…In such patients with cough-variant asthma or EB, therapy exclusive of systemic steroids should be optimized by meticulous attention to ICS compliance and inhaler technique, environmental factors, etc. Measurement of exhaled nitric oxide can support the use of antiinflammatory therapy, as the presence of elevated exhaled nitric oxide levels is predictive of a favorable response to ICS [19]. 8.…”
Section: Clinical Observationsmentioning
confidence: 99%
“…Recently, exhaled nitric oxide has been proposed as a useful biomarker to confirm the presence of eosinophilic airway inflammation and thus, predict a favourable response to inhaled corticosteroid therapy in both asthmatic cough as well as cough due to non‐asthmatic eosinophilic bronchitis (Lim, 2010). Absence of a response to systemic corticosteroids should prompt evaluation for other aetiologies of chronic cough.…”
Section: Chronic Coughmentioning
confidence: 99%